Mapping the information landscape of the United Nations Decade on Ecosystem Restoration Strategy - Meli, P.; Schweizer, D.; Winowiecki, Leigh Ann; Chomba, S.; Aynekulu, E.; Guariguata, Manuel R. (Wiley, 2023)
The strategy of the United Nations Decade on Ecosystem Restoration identifies three pathways for action for overcoming six global barriers thought to hamper upscaling. We evaluated 6,023 peer-reviewed and gray literature papers published over the last two decades to map the information landscape underlying the barriers and associated pathways for action across world regions, terrestrial ecosystem types, restorative interventions and their outcomes. Overall, the literature addressed more the financial and legislative barriers than the technical and research-related ones, supporting the view that social, economic and political factors hamper scaling up ecosystem restoration. Latin America, Africa, and North America were the most prominent regions in the literature, yet differed in the number of publications addressing each barrier. An overwhelming number of publications focused on forests (78%), while grasslands (6%), drylands (3%), and mangroves (2%) received less attention. Across the three pathways for action, the action lines on (1) promoting long-term ecosystem restoration actions and monitoring and (2) education on restoration were the most underrepresented in the literature. In general, restorative interventions assessed rendered positive outcomes except those of a political, legislative or financial nature which reported negative or inconclusive outcomes. Our indicative assessment reveals critical information gaps on barriers, pathways, and types of restorative interventions across world regions, particularly related to specific social issues such as education for ecosystem restoration. Finally, we call for refining “strength of evidence” assessment frameworks that can systematically appraise, synthesize and integrate information on traditional and practitioner knowledge as two essential components for improving decision-making in ecosystem restoration.